(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
Anthropic pressure to irrigate extensive monoculture banana and cocoa plantations from the surface hydrographic network of the canton of Valencia has substantially diminished the flow and water mirrors of the main surface water bodies of the canton. The need to generate foreign exchange to maintain the socioeconomic functioning of the country must address both internal and external factors such as rapid population growth and increasing international demand for tropical agricultural products. The present investigation involved extensive field inventory work of the global study area to select a specific sampling area that is representative of the central problem of the present investigation, and involved the collection of extensive digital geoinformation for subsequent processing in a GIS environment, The digital spatial treatment of the main agricultural coverages of the canton of Valencia dominated by banana and cocoa monocultures to determine their territorial expansion in time and space, as well as the temporo-spatial analysis of the variation of the water mirrors of the San Pablo and Quindigua rivers and the modeling of the flow of the micro-watershed of the Quindigua river located in the sampling area.